Linking diversity and distribution to understand biodiversity gradients and inform conservation assessments - Fabricio Villalobos (Frontiers of Biogeography)
Broad-scale patterns of species richness result from differential coexistence among species in distinct regions of the globe, determined by the species’ ranges and their properties such as size, shape and location. Thus, species richness and ranges are inherently linked. These two biodiversity features also yield primary information for conservation assessments. However, species richness and range size have been usually studied separately and no formal analytical link has been established. In my PhD thesis, I applied and extended a recently developed conceptual and methodological framework to study geographical association among species and similarity among sites. This range–diversity framework, along with stochastic simulation modelling, allowed me to jointly evaluate the relationship between diversity and distribution, to infer potential processes underlying composite patterns of phyllostomid bats, and to use this approach to inform conservation assessments for the Mexican avifauna. I highlight the need to explore composite patterns for understanding biodiversity patterns and show how combining diversity and distributional data can help describe complex biogeographical patterns, providing a transparent and explicit application for initial conservation assessments.